Pinnularia (Bacillariophyta, Pinnulariaceae) from the upper and middle course of Negro River and tributaries, Amazon, Brazil - Pereira, Andreia Cavalcante; Torgan, Lezilda Carvalho; Melo, Sérgio de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The present study aimed to carry out an inventory of the genus Pinnularia along the upper and middle courses of the Rio Negro, including two tributaries and eleven streams, and evaluate the distribution of taxa in the sampled environments. The study was based on analysis of permanent slides of phytoplankton and periphyton samplings. The results revealed the presence of 53 specific and infraspecific taxa. Pinnularia romanorum Metzeltin & Lange-Bertalot is the first record for the Brazilian Amazon. As for the distribution, the highest percentage was of rare organisms (58.5%), followed by sporadic (32.1%), and frequent organisms (9.4%). The Rio Negro showed higher species richness compared to its tributaries. Beta diversity showed that the distribution of taxa in the Rio Negro basin was homogeneous (ß-1=19.07). The homogeneity in the distribution of taxa is probably due to the flood period in which the sampling was made, when the river overflows its banks and invades marginal areas, flooding them in varying degrees of intensity. This flow makes different environments richer in microalgae species and their distributions more homogeneous.